PALLIATIVE CARE - Liliana Eleonora Semenescu; Adina Mitrea; Anda Crişan (Oncolog-Hematolog.ro)
The place and role of holistic therapy in the palliative treatment of oncological patients in terminal phase – the result of a personal experience Oncological palliative therapy – clinical case presentation